2022
DOI: 10.1111/jcal.12684
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an online gamified approach embedded with self‐regulated learning support on students' reading performance and intrinsic motivation: A randomized controlled trial

Abstract: Background: Morphological awareness (MA) is the awareness and ability to manipulate morphemes, the smallest units of meaning in a language. It is identified as a strong cognitive precursor of word reading and reading comprehension. The current MA instructions are limited to classroom settings and delivered by teachers or experimenters. Few studies have included technology and its novel features to deliver MA instructions.Objectives: This study proposes a gamified learning approach embedded with selfregulated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The use of motivational notifications and gamification can also aid in stimulating interest and excitement about learning. Previous research suggests that gamified approach embedded with SRL support can leverage students’ intrinsic motivation and lead to better learning (Qiao et al , 2022). In line with prior studies, our findings imply the importance of the self-regulated gamified approach for lifelong learning.…”
Section: Discussionmentioning
confidence: 99%
“…The use of motivational notifications and gamification can also aid in stimulating interest and excitement about learning. Previous research suggests that gamified approach embedded with SRL support can leverage students’ intrinsic motivation and lead to better learning (Qiao et al , 2022). In line with prior studies, our findings imply the importance of the self-regulated gamified approach for lifelong learning.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the third year, most students take the High School Entrance Examination, which covers six subject courses. Consequently, students' SRL skills are not usually emphasized, and learning mostly depends on faceto-face teacher supervision [28,42]. During the pandemic, the school only offered five main subject courses, with no SRL instruction, for seven periods per day (45 min each).…”
Section: The Education Problemmentioning
confidence: 99%
“…Although there is extensive research on improving students' SRL skills in online learning, most studies have focused on either higher education [7,21] or K-12 students in blended-learning settings [22,23]. Furthermore, previous studies have quantitatively examined the relationships between SRL and learning satisfaction, interaction, effectiveness, and other variables [20,24,25], as well as the effects of a specific strategy, discipline, or software [26][27][28][29]. However, few studies have investigated the process of integrating various strategies into teaching practice to support secondary school students' SRL in online learning environments [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Bai and colleagues (2021) [32] found that experiencing positive emotions during online learning was associated with higher motivation and academic performance among high school students during the pandemic. In 2022, another study focused on the role of intrinsic motivation in self-regulated learning: a meta-analysis review [36], a longitudinal study of social and cognitive factors contributing to student motivation and achievement [37]. Other studies conducted were a Study on the Dual-Process Model in the Role of Emotion in Learning Motivation [32], Self-Regulation and Achievement in Online Learning: The Role of Autonomy Support, Motivation, and Cognitive Strategies [38,39].…”
Section: Intrinsic Motivation Self-regulation Social Cognitive Factor...mentioning
confidence: 99%